2018
DOI: 10.1109/tpwrs.2017.2766269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phasor Based Interface Model for EMT and Transient Stability Hybrid Simulations

Abstract: Electromagnetic transient (EMT) and transient stability hybrid simulations are predominantly used to analyze the interactions between HVDC systems and the ac grids. However, the dynamics of the converters will be greatly affected by the waveforms of adjacent ac systems. Waveform distortion as well as time delay caused by interfacing can significantly increase interface errors, resulting in the decrease of the overall accuracy of the simulations. To solve such problems, a dynamic phasor based interface model (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Although a large-scale power system modeling and simulation are useful, it is less flexible than hybrid simulation as power systems become more and more complicated, and as renewable energy resources increase. That is the reason that hybrid simulation and co-simulation has been developed and expand their applications [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Hybrid simulation improves accuracy because equivalents, which represent areas of non-interest in the power system, do not completely show the responses of the actual power system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large-scale power system modeling and simulation are useful, it is less flexible than hybrid simulation as power systems become more and more complicated, and as renewable energy resources increase. That is the reason that hybrid simulation and co-simulation has been developed and expand their applications [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Hybrid simulation improves accuracy because equivalents, which represent areas of non-interest in the power system, do not completely show the responses of the actual power system.…”
Section: Discussionmentioning
confidence: 99%
“…A hybrid simulation is a powerful tool because power electronics applications in the power system require detailed studies with Electro-Magnetic Transient (EMT) simulation investigating the performance of the equipment, and electric utility also has needs of dynamic investigation in the large power system [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Although many hybrid simulation methods and tools exist, improving the accuracy and efficiency of a large power system simulation, those hybrid simulation tools are based on non-real-time.…”
Section: Features Of Hils-dpt Using Rthsmentioning
confidence: 99%
“…A co-simulation of multi-area power systems was investigated in [7], which dealt with the requirement of large-scale simulation resources using real-time simulation at multiple institutions and the confidence for their grid models. In [8], a GD-RTS of HVDC systems were implemented using Ideal Transformer Model (ITM) Interface Algorithm (IA). This work showed that simulation fidelity is robust with large time delay.…”
Section: Related Workmentioning
confidence: 99%
“…Co-simulators may use parallel processing and multi-rate techniques [13] to accelerate their computations. Recent developments in co-simulation are reported in EMT-TS co-simulation [14][15][16][17][18], EMT-dynamic phasor (DP) co-simulation [19][20][21], and EMT-DP-TS co-simulation [22]. Common problems with these models and algorithms include, but are not limited to, (i) reduced accuracy of the overall simulation when disturbances occur near the interface, (ii) possibility of one time-step delay between decoupled systems, (iii) inaccuracies of interaction in the presence of high-frequency waveforms, and (iv) lack of control on the simulation's computational burden.…”
Section: Introductionmentioning
confidence: 99%